Avaliação de um gel com reduzida concentração de fluoreto suplementado com trimetafosfato de sódio sobre a erosão e abrasão do esmalte dentário bovino: estudo in vitro - Pancote, Laís Pasini [UNESP] (2013)
Objectives: The aim of this study was to evaluate the ability of a gel with low fluoride concentration supplemented with sodium trimetaphosphate (TMP) to reduce erosion and abrasion of enamel in vitro. Methods: Bovine enamel disks (n = 120) were selected through surface hardness (DS) and randomized in five treatment groups (n = 24 per group): placebo, 4500 mg F / g + 5% TMP, 4500 mg F / g, 9000 mg F / g, commercial acidulated gel (12000 mg F / g). Half of the enamel disks were subjected to erosive challenges (ERO) by immersion in Sprite Zero (4 times / day, 5 minutes) for 5 days after topical application of gels. The other half of the disks was subjected to challenge using an abrasive brushing machine after the erosive challenges (ERO + ABR). Enamel blocks were analyzed by DS and by profilometry. Data were subjected to analysis of variance, followed by test Student-Newman-Keuls (p <0,05). Results: A dose-response relationship was found between the concentrations of fluoride gels placebo, 4500 mg F / g, 9000 mg F / g, acid gel and surface hardness. The resulting gels 4500 mg F / g, 4500 mg F / g + 5% TMP was similar (p> 0.05) for hardness loss percentage (% DS) in ERO and ERO + ABR, and acid gel showed lower% DS (ERROR and ERO + ABR) when compared to other groups. Treatment with 4,500 μg F/g + TMP produced the lowest wear values when compared to the remaining groups (p<0.001). Groups that have suffered erosion wear had lower values than the groups that have suffered erosion with abrasion. The groups 4500 mg F / g, 9000 mg F / g acid gel had similar wear values (ERO and ERO + ABR). Conclusion: The results indicate that the protective effects of fluoride gel supplemented with TMP are higher than those resulting from the use of conventional formulations after erosive challenges in vitro, with or without subsequent challenges abrasives. The clinical significance of the results still need to be addressed in future studies